"OVERSELL AND UNDERPERFORM”: THE IMPACT OF GREAT SOCIETY ECONOMIC PROGRAMS UPON THE CITY OF DETROIT, 1964-1968 - Joseph Corey; Jason Taylor (Essays in Economic and Business History, 2010)
This article provides a study of the economic impact of the “Great Society” programs of 1960s upon a major urban area: Detroit, Michigan. Mayor Cavanaugh enthusiastically believed that Detroit could serve as a model for other cities to follow with respect to implementing programs designed to move the nation toward goals President Johnson first established at the 1964 of Michigan commencement speech. This paper focuses upon two major economic objectives of Great Society –– enhancements to human capital and urban renewal. Consistent with accounts of the Great Society nationwide, the programs in Detroit did not deliver upon the political rhetoric put forth by the program’s architects. Instead, the economic programs in Detroit illustrate the frequently cited law of unintended consequences. “In your time we have the opportunity to move not only towards the rich society and the powerful society, but upward to the Great Society.” — President Lyndon B. Johnson speaking at the May 22, 1964 commencement speech at the University of Michigan in Ann Arbor. “Economic policy can more than ever become the servant of our quest make American society not only prosperous but progressive, not only affluent but humane, offering not only higher incomes but wider opportunities, its people enjoying not only full employment but fuller lives.” — President Lyndon B. Johnson from the 1965 Economic Report of the President.